Correlates and spatial distribution of the co-occurrence of childhood anaemia and stunting in Ghana - Aaron Kobina Christian; Caesar Agula; Philip-Neri (Elsevier, 2020)
Childhood anaemia and stunting are major public health concerns in Ghana. Using the 2014 Ghana Demographic and Health Survey, we evaluated whether childhood anaemia (Haemoglobin concentration < 110 g/L) and stunting (height-for-age z score < −2) co-occur beyond what is expected in Ghana, and employed spatial analysis techniques to determine if their co-occurrence is spatially correlated. There was no statistically significant difference between the observed and expected frequency of co-occurrence. Among 24-35 month and 36-59-month-old children, belonging to a high wealth household compared to low wealth household was associated with lower odds of the co-occurrence of childhood anaemia and stunting (OR, 95% CI: 0.3[0.1, 0.8] and 0.2[0.1, 0.5], respectively). Children aged 6-23 months with caregivers who had formerly been in union compared to their counterparts with caregivers who have never been in union had higher odds of co-occurrence of anaemia and stunting (5.1, [1.1, 24.3]). Overall, households with high wealth and having a mother with secondary or more education were associated with lower odds of the co-occurrence of childhood anaemia and stunting (OR, 95% CI: 0.4[0.2, 0.8] and 0.5[0.3, 0.9], respectively). There was substantial spatial clustering of co-occurrence, particularly in the northern region of the country. Interventions purposed to improve linear growth and anaemia must identify the specific factors or context which contribute to childhood anaemia and stunting.